Coordinators’ Perspective on the Pedagogical Intervention in the Study Program “Pedagogy with a specialization in the 1st to 6th grades of the Basic General Education” - Camacho Oviedo, Maureen (2013)
This scientific paper is the result of the pedagogical intervention process carried out as part of teacher training in the study programs of the Basic Education Division at Universidad Nacional (Costa Rica). It aims at bringing into focus the tasks of the supervised professional practice process conducted in the study program of “Pedagogy with a specialization in the 1st to 6th grades of the Basic General Education”, from the perspective of the coordinators of this process. The coordination tasks that are essential for the development and successful completion of the professional practice process are analyzed and systematized in three main areas: coordination, induction, and conclusion of the pedagogical intervention tasks.  The opinions of students and faculty members are considered in the evaluation. One of the main contributions of this paper is calling attention to the pedagogical intervention process, which involves not only the joint preparation of a course program, but also a number of coordination strategies among the persons in charge of the pedagogical intervention to complete the process and take advantage of the practice to think carefully on the educational reality. This study has been also an opportunity of analysis and teamwork focused on continuous feedback to students and to the process itself, giving a new shape to the professional practice, and strengthening university training where the pedagogical intervention process of the Basic Education Division is a permanent research platform.